- #1

- 1

- 0

The solution of the system

ax + ay - z = 1

x - ay - az = - 1

ax - y + az = 1

is (x,y,z) = (a,b,a). If a is not an integer, what is the value of a + b.

A) -3/2

B) -1

C) 0

D) 1/2

E) 1

Can anyone help I dont know how to approach this

Ok then you get :

a^2 + ab -a = 1

a - ab - a^2 = -1

a^2 - b + a^2 = 1

I do not see how I can solve for a+ b to get an answer..

ax + ay - z = 1

x - ay - az = - 1

ax - y + az = 1

is (x,y,z) = (a,b,a). If a is not an integer, what is the value of a + b.

A) -3/2

B) -1

C) 0

D) 1/2

E) 1

Can anyone help I dont know how to approach this

Ok then you get :

a^2 + ab -a = 1

a - ab - a^2 = -1

a^2 - b + a^2 = 1

I do not see how I can solve for a+ b to get an answer..

Last edited: